BOOKCO: MAIZE-ORIENTED SOCIAL SKILLS-BASED E-MODULE IN ELEMENTARY SCHOOLS - Roisyatul Izza; Waspodo Tjipto Subtoro; M. Jacky (JURNAL ILMIAH DIDAKTIKA: Media Ilmiah Pendidikan dan Pengajaran, 2024)
Social skills are crucial in students' daily lives, including the ability to communicate effectively, share ideas, collaborate well, and actively participate in community groups. E-Modul is a form of media presentation of self-study teaching materials arranged systematically and presented electronically, developing a social skills e-module focused on maize cultivation. This research can help students develop the necessary skills to interact effectively. This development research aims to produce e-modules based on social skills Corn-Oriented that are valid, practical, and effective. The research method used in this development study follows a development research using a 4D model, consisting of four stages: namely (1) define, (2) design, (3) develop, and (4) disseminate. The subject of this research is the fifth-grade students of Elementary School Gili Barat. The validation results for the validation of the learning design showed an overall score of 82.5%. The average results of the validation scores provided by linguists from linguists, materials experts, and teaching materials design experts were 94.79%. The average score obtained from the questionnaire responses of both teachers and students was 98.69%. In the teacher activity observation sheet results, a perfect score of 100% was recorded, while the student activity observation sheet showed a score of 97.4%. Furthermore, the learning outcomes achieved met the criteria for classical completeness, with a score of 100%. Based on these findings, the development research concludes that the corn-oriented social skills-based e-module is not only valid but also interesting and effective for use in the learning process.